2018
DOI: 10.1002/chem.201800347
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented Retro‐Mumm Rearrangement Revealed by ESI‐MS/MS, IRMPD Spectroscopy, and DFT Calculations

Abstract: Brønsted acids and protic solvents mediate acyl transfer, known as the Mumm rearrangement, from imidates to the corresponding acylamides. This represents a key step in several reactions, for example, the Ugi four-component reaction (U-4CR) and Passerini three-component reaction (P-3CR). Herein, an unprecedented break of the non-reversibility of the Mumm rearrangement is reported. A combination of electrospray tandem mass spectrometry (ESI-MS/MS), infrared multiphoton dissociation (IRMPD) ion spectroscopy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…The Mumm rearrangement is known to be exothermic and it is therefore suggested to provide a source of the driving force of this multicomponent 4-CR transformation, as indicated elsewhere. [87] In a seminal work, De Angelis and coworkers [90] detected and characterized via ESI-MS(/MS) associated with IRMPD (infrared multiphoton dissociation) ion spectroscopy, the imidate intermediate, which characterization was until then most elusive in the retro-Mumm reaction (Scheme 13). The data strongly supported the characterization of this key intermediate.…”
Section: Popular Mcrs Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mumm rearrangement is known to be exothermic and it is therefore suggested to provide a source of the driving force of this multicomponent 4-CR transformation, as indicated elsewhere. [87] In a seminal work, De Angelis and coworkers [90] detected and characterized via ESI-MS(/MS) associated with IRMPD (infrared multiphoton dissociation) ion spectroscopy, the imidate intermediate, which characterization was until then most elusive in the retro-Mumm reaction (Scheme 13). The data strongly supported the characterization of this key intermediate.…”
Section: Popular Mcrs Mechanismsmentioning
confidence: 99%
“…In a seminal work, De Angelis and coworkers [90] detected and characterized via ESI‐MS(/MS) associated with IRMPD (infrared multiphoton dissociation) ion spectroscopy, the imidate intermediate, which characterization was until then most elusive in the retro‐Mumm reaction (Scheme 13). The data strongly supported the characterization of this key intermediate.…”
Section: Popular Mcrs Mechanismsmentioning
confidence: 99%
“…De Angelis and his group are interested (bio)organic mass spectrometry and in the chemistry of natural organic compounds. He has discussed the use of electrospray mass spectrometry for studying reaction intermediates in solution in a Minireview in Angewandte Chemie , and has reported in Chemistry—A European Journal on a retro‐Mumm rearrangement . De Angelis one of the four Presidents of ChemPubSoc Europe, with responsibility for ChemMedChem and ChemSusChem (and was on the Editorial Board of the latter from 2008–2015).…”
Section: Awarded …mentioning
confidence: 99%
“…ESI-MS is a well-established technique for mechanistic studies of organometallic catalytic processes. [18][19][20][21][22] We have previously used real-time mass spectrometric methods to study the Suzuki-Miyaura cross-coupling (SMC) reaction and various other transformations. [23][24][25][26][27][28][29] Our standard method of real-time reaction analysis involves transporting a solution from the reaction flask to an electrospray ionization (ESI) mass spectrometer using pressurized sample infusion (PSI).…”
Section: Introductionmentioning
confidence: 99%